Enhancing neuromuscular recovery after sciatic nerve injury using stem cell therapy: Evidence from a preliminary preclinical study - Firlana, Cut R.; Emril, Dessy R.; Dedy Syahrizal; Sartika, Cynthia R.; Lestari, Nova D.; Habibie, Yopie A. (Narra Sains Indonesia, 2026)
Sciatic nerve injury results in motor dysfunction and muscle atrophy, with limited effective therapies. Umbilical cord–derived mesenchymal stem cells (UC-MSCs) may promote neuromuscular recovery, but their effects on functional and muscle recovery remain unclear. This study aimed to evaluate the effects of UC-MSC therapy on functional and muscle recovery in an animal model of sciatic nerve injury. An animal experimental study with a post-test-only control group was conducted using adult male Wistar rats. Rats were randomly allocated into three groups: sham operation, saline control with sciatic nerve injury, and UC-MSC treatment after sciatic nerve injury. UC-MSCs were administered at a dose of 1×10⁶ cells/kg body weight immediately after nerve injury. Functional recovery was assessed using the extensor postural thrust (EPT) test, and muscle recovery was evaluated using the gastrocnemius muscle index (GMI) post 35 days of observation. Data were analyzed using one-way ANOVA for EPT percentage recovery and Kruskal–Wallis tests for GMI values, followed by post-hoc analysis. Our data indicated there was no significant EPT percentage recovery among the study groups. In contrast, relative gastrocnemius muscle mass was significantly different across groups (p=0.012), with post-hoc analysis demonstrating a significantly higher GMI in the UC-MSC group compared to the saline control group (109.75% vs 81.68%, p=0.003), indicating improved preservation of gastrocnemius muscle mass following UC-MSC therapy. This study highlights that UC-MSC therapy significantly improved gastrocnemius muscle preservation after sciatic nerve injury but did not result in detectable functional motor recovery at the observation time point. These findings suggest that UC-MSCs might exert early structural benefits that may precede functional recovery.